HISTOLOGICAL STRUCTURE AND HISTOMORPHOMETRY THE BASIS, CORPUS, AND APEX CAECUM OF BALI CATTLE - Kencana, Ngurah Arbi; Setiasih, Ni Luh Eka; Heryani, Luh Gde Sri Surya (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023, 2023)
This study aims to determine the histological structure and histomorphometry as well as differences in histomorphometry of the cecum of Bali cattle at the basis, corpus and apex. For this study the female balinese cattle caecum of 10 (4-5 years) were collected from Pesanggaran Animal Slaughterhouse. Caecum samples taken basis, corpus and apex for subsequent fixation using a solution Neutral Buffered Formalin 10%, then stained using Haematoxillin-Eosin. The results are presented in a qualitative descriptive and quantitative descriptive method. Caecum was composed of 4 layers; tunica mucosa, submucosa, muscularis and serosa. Histomorphometrical measurements showed that the thickness of the mucosa, submucosa, muscularis and serosa in the basis part were 376,87±34,411?m, 1508,73±349,022?m, 2767,76±609,698?m, 199,95±21,502?m, in the corpus were 380,36±51,501?m, 739,28±129,371?m, 2287,66±303,987?m, 328,19±77,468?m and in the apex were 407,05±63,902?m, 615,57±205,736?m, 2730,51±332,044?m, 297,82±51,211?m. Histomorphometry of the tunica mucosa, tunica submucosa, tunica muscularis and tunica serosa showed that there was no significant difference in the tunica mucosa at the basis, corpus and apex, the thickness of the tunica submucosa at the basis was thicker than the corpus and apex, and the thickness of the tunica muscularis at the basis and apex. thicker than the corpus, there is no significant difference in the serous tunica at the basis, corpus and apex. It is necessary to do macro and micro anatomical research on the large intestine of Bali cattle by paying attention to rearing management, differentiating age, sex, and doing special coloring.